UPAYA PENINGKATAN HASIL BELAJAR GERAK DASAR LARI DAN LOMPAT MELALUI PERMAINAN TRADISIONAL - Abdul Malik (PHEDHERAL, 2017)
The purpose of this study is to improve the learning results of basic motion run and jump through the traditional game in learning pemas on third grade students MIN SROYO Jaten Karanganyar teaching 2016/2017. This research is a Classroom Action Research (CAR). This study was conducted in two cycles, consisting of four stages in each cycle consisting of planning, action implementation, observation and reflection. Subjects in Action Research This class is the third grade students MIN SROYO Jaten Karanganyar, amounting to 31 students consisting of 16 students and 15 female students. Sources of data in this study come from students, researchers and teachers who act as collaborators. Techniques of collecting data using tests and observations. Data validity using data triangulation technique. Data analysis using qualitative descriptive technique based on qualitative analysis percentage. Result of research on prasiklus only 11 complete student (35.49%) and 20 students unfinished (64,51%). In the first cycle obtained the results of student learning that has been completed as many as 18 students (58.07%) and 13 students are not complete (41.93%). With the acquisition of affective averages (77.42%), psychomotor (35.49%) and cognitive (83.87%). In the second cycle obtained the results of student learning that has been completed as many as 26 students (83.87%) and 5 students is not complete (16.13%). With the acquisition of affective averages (96.77%), psychomotor (74.19%) and cognitive (83.87%) Based on the analysis results from cycle I and cycle II showed a significant increase and target achievement. Based on the results of the research obtained the conclusion that: The use of simple aids in learning can improve the learning results of basic motion run and jump on the students of class III MIN SROYO Jaten Karanganyar academic year 2016/2017.